Fish Segmentation And Classification For Large Scale Dataset From Turkey - Nur Amirah Shafiqah, Salleh (2022)
Classification helps humans learn about different kinds of fish, their features, similarities, and differences. In this project, images from eight fish types are collected from a supermarket’s fish counter; every kind of fish has 1000 images. This study aims to extract fish’s texture, color, and shape and utilize K-Nearest Neighbors (KNN) and Support Vector Machine (SVM) classifiers to categorize the eight different types of fish in Izmir, Turkey. The results from the experiment show the accuracy of KNN is 100% and SVM is 100%.